(untitled) (Conferencea, 2024)
This paper delves into the realm of chronic allergic rhinitis, offering a comprehensive overview while focusing specifically on its incidence rate. Chronic allergic rhinitis poses a significant health burden worldwide, impacting individuals’ quality of life and healthcare systems. Understanding its prevalence and patterns of occurrence is crucial for effective management and resource allocation. Through a synthesis of existing literature and data analysis, this paper aims to shed light on the epidemiological landscape of chronic allergic rhinitis, providing valuable insights for healthcare professionals, policymakers, and researchers alike.